Religion Norms in Foreign Policy Analysis: Dispensationalism As US Foreign Policy’s Determinant During Trump's Reign - Afif Sabwanto, (Technium Social Sciences Journal, 2023)
During Trump Administration, he introduced and used “America First” as his guidance in conducting US Foreign Policy. The “America First” emphasizes pursuing national interests and using force to achieve security and prosperity. However, Trump's decision to relocate the US Embassy and recognition Jerusalem as Israel’s capital city was contradictory with his "America First" strategy. The author’s main question is that What sort of norm shaped US embassy relocation policy? It seems dispensationalism played pivotal role in influencing US embassy relocation policy. Dispensationalism believe that the restoration of Israel is a necessary precondition for the Lord's return and that the Jews must return to their homeland to be regathered as a nation. Trump’s motive to adopt Dispensationalism as part of conducting US foreign policy was driven by the urgency to maintain his voting bloc after 2016 US Election.